산화아연이 함유된 글래스 아이오노머 수복재의 항균 및 물성평가 - 최유리(Yu-Ri Choi); 강민경(Min-Kyung Kang) (한국구강보건과학회지, 2024)
Objectives: This study aimed to investigate the antibacterial and physical properties of glass ionomer restoratives containing zinc oxide. Methods: The concentration of zinc oxide in the glass ionomer was adjusted to create experimental groups with 0% (control), 1%, 2%, and 3% zinc oxide. Physical properties were evaluated by measuring surface hardness, surface roughness, and color difference, while antibacterial properties were tested by exposing Streptococcus mutans to the extract of the specimens for 24 hours and measuring the absorbance. Additionally, a clear zone test was conducted using specimens containing glass ionomer. Results: The experimental group with 3% zinc oxide showed a significant increase in surface hardness compared to the control group, with no significant differences in surface roughness or color difference. In the antibacterial test, the 3% zinc oxide group demonstrated a significantly lower bacterial survival rate compared to the control group, and a clear antibacterial zone was observed. Conclusions: It was confirmed that the glass ionomer restorative material containing zinc oxide had antibacterial properties and improved physical properties. These findings provide essential foundational data for the future development and clinical application of dental restorative materials. KCI Citation Count: 0